2010
DOI: 10.1021/jf100073j
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Synthesis of Flavonoid Derivatives, QSAR Study and Insecticidal Activity against the Fall Armyworm, Spodoptera frugiperda (Lep.: Noctuidae)

Abstract: A simple, clean, solvent-free preparation of flavones by the use of a silica-supported Preyssler heteropolyacid as reusable catalyst is described. High selectivity and very good yields (87-94%) were obtained in short reaction times (7-13 min). Bioassays for insecticidal activity against Spodoptera frugiperda were carried out with a set of flavones. Bioassays showed that some of the flavones had moderate insecticidal activity. Quantitative structure-activity relationships were established on the available data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…Insecticidal activities of target compounds and positive controls (fipronil, 96% purity and chlorantraniliprole, 95% purity) against Spodoptera frugiperda were tested indoors according to the literature 34 . Each of the test compounds was dissolved in DMSO and diluted to 100 mg L −1 with distilled water containing Tween 80 (0.1%, v/v ).…”
Section: Methodsmentioning
confidence: 99%
“…Insecticidal activities of target compounds and positive controls (fipronil, 96% purity and chlorantraniliprole, 95% purity) against Spodoptera frugiperda were tested indoors according to the literature 34 . Each of the test compounds was dissolved in DMSO and diluted to 100 mg L −1 with distilled water containing Tween 80 (0.1%, v/v ).…”
Section: Methodsmentioning
confidence: 99%
“…The flavonoids have a protector effect from ultraviolet light and microbial damage, and some synthetic derivatives have shown insecticide activity. For example, Romanelli et al [ 27 ] obtained a series of 9 flavonoid derivatives of 1-(2-hydroxyphenyl)-3-aryl-1,3-propanediones. Its base structure is shown in Figure 3 .…”
Section: Chemical Insecticidesmentioning
confidence: 99%
“…In this study, the insecticidal activities of the target compounds 8a and 8b and 9a-9t against P. xylostella (thirdinstar Larvae) and S. frugiperda (second-instar larvae) were evaluated using the previously reported methods. [26,27] Meanwhile, chlorantraniliprole was used as a positive control under the same conditions. The results of the preliminary bioassays, as listed in Table 1, indicated that the target compounds 8a and 8b and 9a-9t showed insecticidal activities against P. xylostella at 200 mg/L and 50 mg/L with the values of 0% to 93.64% and 0% to 72.59%, respectively, which were all lower than chlorantraniliprole (mortality rate, 100% and 96.67%, respectively).…”
Section: Insecticidal Activities and Sar Analysismentioning
confidence: 99%